Do delayed antibiotic prescriptions decrease antibiotic use for respiratory infections?. Issue 2 (February 2018) - Torres, Yanelquis A.; Adam, Patricia
Abstract : EVIDENCE‐BASED ANSWER : Several techniques for delaying antibiotic prescriptions decrease the use of antibiotics for treatment of upper respiratory infections (URI) compared with immediate antibiotic prescriptions in adults and children. No difference was noted in the overall rate of antibiotic use when comparing delayed versus no antibiotic prescription, nor when comparing different methods of delayed antibiotic prescriptions (SOR: A, systematic review of RCTs and single RCT).